Near-zero nonlinear error pressure sensor based on piezoresistor sensitivity matching for wind tunnel pressure test - Yuanying Zhang; Fengyun Liu; Zechen Zhou; Xiubing Liang; Riming Sun; Jinjun Deng; Xiaoliang Luo; Jian Lin; Xing Chen; Xingxu Zhang; Jian Luo; Xiaojing Wang; et al. (Microsystems & Nanoengineering)
Abstract High-precision piezoresistive pressure sensors play a significant role in aerospace, automotive, and other fields. Nonlinear error is the key factor that restricts the improvement of the sensor precision. A mathematical model for evaluating the sensor’s nonlinear error is established, based on which a piezoresistor sensitivity matching method is proposed to suppress the nonlinear error. By adjusting the piezoresistors' structure and position on the sensing membrane, four piezoresistors with equal sensitivity are obtained, and theoretical quasi-zero nonlinear error is achieved. To verify the design, sensor prototypes are fabricated utilizing the MEMS technology. After sensor packaging, a cylindrical absolute pressure sensor featuring a 4 mm diameter with a range from 0 to 100 kPa is acquired. The experimental results demonstrate the excellent performance of the proposed sensor, which indicates a nonlinear error as low as ±0.004%FS. Besides, the proposed sensor has a sensitivity of 1.6810 mV/kPa, a hysteresis of 0.025%, a repeatability of 0.015%, a zero drift of 0.03%FS, and a 3 dB frequency from 0 to 121.82 kHz. Moreover, the prototype is tested in the Mach 4 wind tunnel, and the measurement error between the proposed sensor and the true pressure is ±0.98%. This paper provides key sensing technology for high-precision surface pressure analysis of aircraft.